Pushover Analysis of RC Building Frames With Symmetrical Setback - Ahmed G. Fouad, Nayer A. El-Esnawy, Bahaa E. H. Mahmoud (International Journal of Advanced Science and Technology, 2020)
Due to architectural needs, the geometrical irregularities in buildings, either in plan or elevation, have become among the common challenges that face structural engineers nowadays. Irregularities in elevation are usually associated by the presence of setbacks in the building. In this paper, the seismic responses of several R/C multi-storey moment-resisting frame buildings with single symmetrical setback are examined and evaluated via pushover analysis, which is a non-linear static analysis technique used to estimate the seismic capacity of buildings for design purposes. Four pushover analysis methods are applied for different vertical configurations of setbacks: the mass proportional uniform pushover analysis, the mass proportional triangular pushover analysis, the method of modal combinations, and the improved upper bound method. Also, the nonlinear time-history analysis using seven scaled earthquakes is applied to determine the mean values and standard deviations for the seismic responses. The results of the inter-story drifts for damage and the base shear for strength determined by the pushover analysis methods are compared with the mean results determined by the nonlinear time-history analysis. This comparative study with the nonlinear time-history analysis shows that the improved upper bound pushover method is the most suitable to estimate damage based on inter-story drifts for R/C multi-storey moment-resisting frame buildings with setbacks, whereas the mass proportional uniform pushover method is better for estimating the base shear capacities of buildings.